Materialität, Inschriftlichkeit und schrifttragende Artefakte im mittelalterlichen Rom - Zöller, Wolf (Materiale Textkulturen, 2023)
Like ancient Rome, the medieval metropolis on the Tiber is also a landscape of transmission due to the diversity of its epigraphic legacy. This legacy had a lasting impact on the municipal area of the urbs and provides contemporary researchers with information about the practices of communication that developed in the city. This volume examines this multifaceted medieval epigraphic culture with help from new methodological impulses.